1997
DOI: 10.1007/s11663-997-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics on the formation of spinel nonmetallic inclusion in liquid steel

Abstract: The nonmetallic spinel inclusion, MgO⅐Al 2 O 3 , has a high melting point and produces an undeformed C-type inclusion in steel products. Therefore, it is very harmful in the production of high grade wire, spring, and bearing steels. Thus, it is necessary to develop a methodology by which we can predict the occurrence of such defects.The thermodynamics of the formation of spinel nonmetallic inclusions during co-deoxidation with aluminum and magnesium is discussed in the present work. Previous literature thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(146 citation statements)
references
References 4 publications
4
140
0
2
Order By: Relevance
“…The formation of MgO·Al 2 O 3 spinel in Al-killed steel has been studied by many researchers. 7,9,10,21) Most of them believed that if there is a trace of dissolved Mg in steel, alumina inclusions tend to transform into spinel inclusions. In the present study, as shown in Table 3, before LF refining and at the middle of LF, several ppm dissolved Mg has been generated.…”
Section: Evolution Of Inclusions In Medium Mn Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of MgO·Al 2 O 3 spinel in Al-killed steel has been studied by many researchers. 7,9,10,21) Most of them believed that if there is a trace of dissolved Mg in steel, alumina inclusions tend to transform into spinel inclusions. In the present study, as shown in Table 3, before LF refining and at the middle of LF, several ppm dissolved Mg has been generated.…”
Section: Evolution Of Inclusions In Medium Mn Steelmentioning
confidence: 99%
“…Some of them [7][8][9][10]12,21,29) thought that the formation of MgO·Al 2 O 3 spinel inclusions depends on the concentration of dissolved Mg, Al and O in liquid steel. Meanwhile, some researchers 18,19,21) found that MgO·Al 2 O 3 spinel could still precipitate from CaO-SiO 2 -Al 2 O 3 -MgO system inclusions during the cooling of liquid steel, although the composition of Mg, Al and O in steel was not in the stable region of MgO·Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…72,[75][76][77][78][79] Particle growth occurs at microscales depending on the microscale phenomena of bubble attachment, turbulent collisions, 27,72,75,76 interface reactions, reoxidation, and local thermodynamics. 20,[80][81][82][83] Finally, inclusion transport and removal at the slag or by bubble flotation 24,26,84,85 and particle entrapment in solidifying dendritic interfaces [3][4][5]73 depend on flow transport and on the nature of the flow pattern and shape of the metallurgical vessel. Different nano-and microscale models have been used to predict important specific phenomena.…”
Section: -10mentioning
confidence: 99%
“…Table 3 shows the Gibbs free energy of chemical reactions involved in the present work. Table 3 Free energy data of reactions considered in the present work [4,5,6,7] Reaction…”
Section: Resultsmentioning
confidence: 99%